Immune memory shapes human polyclonal antibody responses to H2N2 vaccination - Yang, Yuhe R.; Han, Julianna; Perrett, Hailee R.; Richey, Sara T.; Rodriguez, Alesandra J.; Jackson, Abigail M.; Gillespie, Rebecca A.; O’Connell, Sarah; Raab, Julie E.; Cominsky, Lauren Y.; Chopde, Ankita; Kanekiyo, Masaru; et al. (Cell reports (Cambridge), 2024)
Influenza A virus subtype H2N2, which caused the 1957 influenza pandemic, remains a global threat. A recent phase 1 clinical trial investigating a ferritin nanoparticle vaccine displaying H2 hemagglutinin (HA) in H2-naive and H2-exposed adults enabled us to perform comprehensive structural and biochemical characterization of immune memory on the breadth and diversity of the polyclonal serum antibody response elicited. We temporally map the epitopes targeted by serum antibodies after vaccine prime and boost, revealing that previous H2 exposure results in higher responses to the variable HA head domain. In contrast, initial responses in H2-naive participants are dominated by antibodies targeting conserved epitopes. We use cryoelectron microscopy and monoclonal B cell isolation to describe the molecular details of cross-reactive antibodies targeting conserved epitopes on the HA head, including the receptor-binding site and a new site of vulnerability deemed the medial junction. Our findings accentuate the impact of pre-existing influenza exposure on serum antibody responses post-vaccination. [Display omitted] •Variable HA head epitopes targeted in H2-exposed donors after H2-F vaccination•Conserved head and stem epitopes targeted in H2-naive donors after H2-F vaccination•RBS-targeting VH1-69 cross-reactive antibodies induced in H2-naive individuals•The medial junction is a previously uncharacterized conserved epitope on HA Yang et al. structurally characterize antibody responses to H2N2 vaccination in H2-naive and H2-exposed people, demonstrating temporal immune biases to conserved and variable regions on HA. H2N2 vaccination elicited antibodies to conserved sites on the HA stem, receptor-binding site, and medial junction.